Quantify The Spatio-Temporal Trends And Patterns Of Urban Growth In Adama City Using Satellite Remote Sensing And Spatial Metrics, Ethiopia. - Tarekegn, Fita (ASTU, 2017)
The Spatio-Temporal Patterns And Processes Of Urban Growth Of Adama City And Its Drivers Were Investigated From 1988 To 2017 By Using Satellite Remote Sensing Images, Spatial Metrics And Logistic Regression Modeling (Lrm). Four Different Land Cover Maps Derived From Landsat Tm Image Of 1988, Landsat Etm+ 2000, 2010 And Landsat Oli/Tir Of 2017 Were Used To Evaluate A Set Of Five Selected Spatial Metrics To Reveal Patterns And Dynamics Of Urban Growth In The Study Area. The Computation Of Spatial Metrics Was Conducted At Two Spatial Scales. First, The Summary Descriptors Of Landscape Heterogeneity At The City Level Are Evaluated. Secondly, In Order To Better Link The Metric Analysis To More Specific Locations, The Study Area Is Broken Into Three Smaller Individual Regions On The Basis Of Administrative Boundaries. Then The Changing Patterns Of Urban Growths Over Time Were Linked To The Major Physical Driving Forces In The Study Area With Binary Logistic Regression Modeling. Therefore Three Models Were Built For 1988-2000, 2000-2010 And 2010-2017 Time Periods. The Growth Was Prolonging Both From Urban Center To Adjoining Nonbuilt Up Areas In All Direction, But Mainly To The West, East And North Direction Alongside Major Transportation Corridors. The Total Built Up Area In The City Has Grown From 415.44 Ha In 1988 To 5599.62 Ha In 2017 At An Average Growth Rate Of 2.36%, 5.97% And 6.27 % Per Annum During 1988-2000, 2000-2010 And 2010-2017 Study Periods Respectively. The Study Period From 2000 To 2010 Was Registered As The Time At Which The City Experienced The Highest Urban Growth. The Analysis Of Spatial Metrics At The City Level Revealed That The Urban Landscape Has Experienced A Process Of Sprawling And Fragmented Development Pattern Particularly In The Fringe Areas While, The City Center Under Went In Fill And Edge Expansion Development Processes. The Core Area Consolidated Over Time While The Northern Region Relatively Underwent Compact Growth And The Fringe Areas Show Scattered Growth Pattern. The Results Of Binary Logistic Regression Model Revealed That Distance To Major Roads, Distance To Sub City Centers, Proportion Of Built Up Cell, Distance To Cbd, Distance To Satellite Towns And Slope Were The Major Driving Forces Of Urban Growth At Different Time Periods With Varying Level Of Significance And Correlation.
Keywords: Urban Growth, Spatial Metric, Remote Sensing, Land Cover Change, Logistic Regression